Influence of different shot peening treatments on surface state and fatigue behaviour of Al 6063 alloy. (November 2017) - González, Juan; Bagherifard, Sara; Guagliano, Mario; Fernández Pariente, Ines
Highlights: Different shot peening treatments are used to study surface modifications. Severe shot peening is able to generate a surface layer with ultra fine grains. Fatigue tests data are critically discussed in the light of surface characteristics. Insight is provided towards better understanding of severe shot peening. Abstract: Shot peening is a surface treatment commonly used to improve the fatigue behaviour of mechanical components. It consists in bombarding metallic surfaces with spherical shots to induce plastic deformation in the surface layer of the material. Recent studies have shown that, if applied with unconventional parameters, namely severe shot peening, it can be considered a severe plastic deformation surface treatment, able to strongly modify the microstructure of the surface layer of material by generating grains in the scale of nanometers. In this paper, different shot peening treatments with conventional and severe parameters were performed on aluminium 6063 alloy in order to assess the differences induced in the microstructure of the surface layer, and to evaluate their effects on fatigue behaviour. Rotating bending fatigue tests were performed on shot peened hourglass specimens. Specimens' microstructure, surface roughness, microhardness and residual stress profiles were carefully characterized. The obtained results evidence the notable influence of shot peening parameters on surface layer microstructure, which at the same time influences fatigue behaviour.